Research and Practice in K-12 Online Learning: A Review of Open Access Literature - Cavanaugh, Cathy S.; Barbour, Michael K.; Clark, Tom (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2009)
The literature related to online learning programs for K-12 students dates to the mid-1990s and builds upon a century of research and practice from K-12 distance education. While K-12 online learning programs have evolved and grown over the past decade, the amount of published research on virtual schooling practice and policy is limited. The current literature includes practitioner reports and experimental and quasi-experimental studies, both published and unpublished. This paper reviews open access literature in K-12 online learning and reports on a structured content analysis of the documents. Themes in the literature include steady growth and a focus on the benefits, challenges, and broad effectiveness of K-12 online learning. In addition, newly developed standards for K-12 online learning are emerging in descriptions of effective practices.